Oxygen vacancy-dependent photocatalytic activity of well-defined Bi2Sn2O7−x hollow nanocubes for NOx removal. Issue 7 (8th June 2021) - Lu, Yanfeng; Chen, Meijuan; Huang, Tingting; Huang, Yu; Cao, Jun-ji; Li, Haiwei; Ho, Wingkei; Lee, Shun Cheng
Abstract : Bi2 Sn2 O7− x with Sn-/Bi-adjacent oxygen vacancy were designed and applied for photocatalytic removal of rarefied NO. DFT and experiments provided a straightforward and clear understanding of the structure-performance relationship of oxygen vacancies. Abstract : Intricate engineering of oxygen vacancies (OVs) to trap kinetically diffusible rarefied NO gas and to enhance the population of long-lived electrons remains a great challenge for NO removal in outdoor atmosphere. In this study, OV-engineered Bi2 Sn2 O7− x hollow nanocubes with distinct Sn/Bi-adjacent OVs were tightly managed and synthesized. Theoretical calculations and experimental studies revealed that not all types of OVs were beneficial for increasing the photoactivity owing to their different effects on the band structure and carrier diffusion path. Bi2 Sn2 O7− x with Sn-adjacent OVs could serve as adsorption sites, boosting rarefied NO enrichment and electron–hole separation. However, Bi2 Sn2 O7− x with Bi-adjacent OVs exhibited an opposite effect owing to increased charge recombination centers. Our findings highlight the importance of the character of OVs for efficient interface electron activation and for the removal of ambient rarefied gaseous pollutants.